Fabrication of 2D thin-film filter-array for compressive sensing spectroscopy. (April 2019) - Kim, Cheolsun; Lee, Woong-Bi; Lee, Soo Kyung; Lee, Yong Tak; Lee, Heung-No
Highlights: We propose and design a practical way to fabricate a 2D filter-array for sensing spectroscopy. We fabricate a 2D thin-film filter-array for compressive sensing spectroscopy. We recover the LEDs/monochromatic light sources using a reconstruction algorithm and the fabricated filter-array. Abstract: We demonstrate 2D filter-array compressive sensing spectroscopy based on thin-film technology and a compressive sensing reconstruction algorithm. To obtain different spectral modulations, we fabricate a set of multilayer filters using alternating low- and high-index materials and reconstruct the input spectrum using a small number of measurements. Experimental results show that the fabricated filter-array provides compatible spectral resolution performance with a conventional spectrometer in monochromatic lights and LEDs. In addition, the fabricated filter-array covers a wide range of wavelengths with a single exposure.